Penerapan Failure Mode and Effect Analysis (FMEA) dalam Meningkatkan Efektivitas Manajerial di Perusahaan Kontruksi - Denisa Fajrianti; Wahyudin Wahyudin (Fakultas Teknik Universitas Tulang Bawang, 2026)
The application of Failure Mode and Effect Analysis (FMEA) is essential for identifying critical failures in the implementation of Total Quality Management (TQM) at a construction company in Bogor, which still faces managerial inefficiencies due to weak teamwork, low employee involvement, and inadequate training. This study aims to analyze the failure modes that affect the implementation of TQM using the FMEA method. Data were collected through observations, interviews, documentation, and assessments of the ten TQM principles. The results show three failure modes with the highest Risk Priority Numbers (RPN): low employee involvement RPN = 378, weak teamwork RPN = 336, and insufficient education and training RPN = 210. These failures significantly impact managerial effectiveness and project target achievement. This research provides strategic recommendations such as establishing a suggestion system, conducting weekly coordination meetings, and implementing competency-based training programs. The findings demonstrate that FMEA is effective in determining improvement priorities to strengthen managerial quality and organizational performance. Keywords: Construction Industry, Failure Mode and Effect Analysis, Failure Risk, Managerial Effectiveness, Total Quality Management.